Rye breeding rests on hardy genotypes - Hovinen, Simo; Teperi, Esa (MTT, 2008)
Local races of winter rye have been grown to the present day in many places in Finland. These races of this allogamous and highly heterozygous species are usually strongly adapted to local climate, soil quality conditions and cultivation practices. Local races are derived from old, mainly European local races or varieties which have been imported to Finland during the history of rye cultivation here. The single plants which have not been able to survive over hard winters or which lacked growth vigour during stand development have not produced seed. This elimination of weak plants has continued from generation to generation raising the fitness of the population and increasing adaptation. Because of cross pollination rye plants will become very similar by phenotype if there is no pollen transfer from the outside. Different parts of Finland have varied growing conditions which has led to different adaptation of local races and our country has become a valuable source of rye polymorphism. Rye breeders in our country have repeatedly used local races as gene sources for winter hardiness, earliness and disease resistance. Domestic market varieties which have been grown widely and successfully are reliable cross parents as well. Our long lasting winter is often too severe to varieties from more southern countries. A winter rye variety for Finland must be hardy against extreme cold in the winters without snow cover and resistant against snow mould in the winters when snow cover stands long. Here in the North rye varieties must also be adapted to long day lengths to be able to exploit all the sun light for rapid growth. The Finnish rye breeding has been much based on crosses between local land races or domestic varieties and foreign, high yielding varieties possessing high resistance against lodging. The goal is to breed a modern rye variety with high adaptability and stabile yield level. The crosses between non-relatives guarantee a high degree of continuous heterozygocity and heterosis in varieties descending from such crosses which raises their yield level in cultivation. Seeds of local races were collected and saved from being lost by collecting expeditions soon after founding of the Nordic Gene Bank. Now the collections of the Nordic Genetic Resource Centre (NordGen) include 90 local races and 34 varieties of rye from our country. A part of the collection has been evaluated for field characteristics in Jokioinen in 1999. As a breeder s view, the local race from Kinahmi, Nilsiä, was a good candidate among some others for a cross parent. Today, local races are still grown for production in many provinces. Seed samples of those are acquired by the working group of genetic resources in question. The samples are usually rejuvenated by distance isolations to get the sample of high quality for long term storage in NordGen. As an example, there have been three such distance isolations in the South Savo experimental station of MTT Agrifood Research Finland this summer. One of them, a local race originating from Iissavaara, Lieksa, showed exceptionally high tillering capacity and resistance against diseases.
Keywords: Pu; winter rye; local races; gene resources of rye; adaptability of rye